Kształtowanie pojęć w kontekście itinerarium wiary - Krzysztof Kantowski (Colloquia Theologica Ottoniana, 2014)
Year of Faith in Church resulted in deep look at the reality of faith and ways of its transmission. One way to look at the pedagogy of faith can be confronting this process with the achievements of pedagogical science in various ways in educational processes. The article shows not only the role of shaping religious concepts in the process of mature faith but also the opportunities of catechesis in Catechism of the Catholic Church.